Indigenous Resource Management System in Selected Backwater Stake net Fisheries of Kerala - Thomas, Saly N.; Archana, G.; Edwin, Leela (Fishery Technology, 2019)
Application of indigenous knowledge is common among the traditional fishers operating indigenous fishing systems. Stake net is an important gear operated along the backwaters of Kerala. Stake net fishers follow many traditions in the fabrication, operation and maintenance of the fishing unit. Lunar periodicity based fishing operation and paadu systems envisage resource conservation through control of fishing effort. The fishing canoe and the gear are protected against biodegradation using ecofriendly natural protective coatings thereby protecting the biota from the ill-effects of synthetic dyes and chemical preservatives.